Impact of peak provoked left ventricular outflow tract gradients on clinical outcomes in hypertrophic cardiomyopathy. (15th September 2017) - Lu, Dai-Yin; Hailesealassie, Bereketeab; Ventoulis, Ioannis; Liu, Hongyun; Liang, Hsin-Yueh; Nowbar, Alexandra; Pozios, Iraklis; Canepa, Marco; Cresswell, Kenneth; Luo, Hong-Chang; Abraham, M. Roselle; Abraham, Theodore P.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is traditionally classified based on a left ventricular outflow tract (LVOT) pressure gradient of 30 mmHg at rest or with provocation. There are no data on whether 30 mmHg is the most informative cut-off value and whether provoked gradients offer any information regarding outcomes. Methods: Resting and provoked peak LVOT pressure gradients were measured by Doppler echocardiography in patients fulfilling guidelines criteria for HCM. A composite clinical outcome including new onset atrial fibrillation, ventricular tachycardia/fibrillation, heart failure, transplantation, and death was examined over a median follow-up period of 2.1 years. Results: Among 536 patients, 131 patients had resting LVOT gradients greater than 30 mmHg. Subjects with higher resting gradients were older with more cardiovascular events. For provoked gradients, a bi-modal risk distribution was found. Patients with provoked gradients > 90 mmHg (HR 3.92, 95% CI 1.97–7.79) or < 30 mmHg (HR 2.15, 95% CI 1.08–4.29) have more events compared to those with gradients between 30 and 89 mmHg in multivariable analysis. The introduction of two cut-off points for provoked gradients allowed HCM to be reclassified into four groups: patients with "benign" latent HCM (provoked gradient 30–89 mmHg) had the best prognosis, whereas those with persistent obstructive HCM had the worst outcome. Conclusions: Provoked LVOT pressure gradients offer additional information regarding clinical outcomes in HCM. Applying cut-off points at 30 and 90 mmHg to provoked LVOT pressure gradients further classifies HCM patients into low-, intermediate- and high-risk groups.